Penerapan Eksekusi Jaminan Fidusia Pada Benda Bergerak Terhadap Debitur Wanprestasi - Ismail Koto; Faisal Faisal (Mahesa Research Center, 2021)
This article or writing aims to discuss the Fiduciary Guarantee Law which has provided rules regarding the execution of the Fiduciary Guarantee object, but the fact is that in the field executions carried out by financial institutions do not comply with the applicable laws and regulations. carried out by financial institutions deviations and acts against the law occur. The obligation to register fiduciary guarantees is strengthened by the existence of PMK RI Number 130/PMK.010/2012 concerning Registration of Fiduciary Guarantees for finance companies that carry out consumer financing for motor vehicles with the imposition of fiduciary guarantees. The discussion focuses on how the provisions of Indonesian National law regulate the execution of fiduciary guarantees on movable objects against defaulting debtors? and how is the execution mechanism of fiduciary guarantees on movable objects against defaulting debtors. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. This paper will then be analyzed qualitatively. The purpose of this study is to find out the provisions of Indonesian National law governing the execution of fiduciary guarantees on movable objects against defaulting debtors and the mechanism of execution of fiduciary guarantees on movable objects against defaulting debtors. This study concludes that Fiduciary is the transfer of ownership rights to an object on the basis of trust provided that the object whose ownership rights are transferred remains in the control of the owner of the object. Article 1 of Law Number 42 of 1999 concerning Fiduciary Security (Law Number 42 of 1999 concerning Fiduciary Guarantee ). While Fiduciary Guarantee is a guarantee right on movable objects, both tangible and intangible and immovable objects, especially buildings that cannot be encumbered with mortgage rights as referred to in Law Number 4 of 1996 concerning Mortgage Rights which remain in the control of the Fiduciary Giver, as collateral for the repayment of certain debts, which gives priority to the Fiduciary Recipient over other creditors. (Article 1 of Law Number 42 of 1999 concerning Fiduciary Security).